Composition containing sinterable powder and method for producing sintered body
The introduction of fine fibrous cellulose into starch-based sinterable powder slurries addresses the issue of non-uniform gelation by stabilizing starch particle dispersion, resulting in improved sintered body production.
Patent Information
- Application Number
- JP2021104417
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-06-23
AI Technical Summary
The use of starch in sinterable powder slurries for gel casting leads to non-uniform gelation due to the slow gelation time and precipitation of starch particles before complete gelation.
A composition comprising fine fibrous cellulose with specific properties, starch, and a sinterable powder is used, where the fine fibrous cellulose improves the dispersion stability of starch particles and ensures uniform gelation.
The composition stabilizes starch particle dispersion, preventing sedimentation and ensuring uniform gelation, which enhances the production of sintered bodies with improved properties.
Smart Images

Figure 0007650734000001 
Figure 0007650734000002 
Figure 0007650734000003
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a composition including a sinterable powder, and a method for producing a sintered body using the composition. [Background technology]
[0002] In the method of manufacturing ceramic products or metal products by firing, powder molding is used as a technique for creating a shape before firing. Powder molding is a method of converting poorly cohesive sinterable powder (powder) into a cohesive and cohesive object with the desired shape and structure. For example, injection molding, slip casting, gel casting, etc. are known as wet molding methods using a slurry. Among these, gel casting is a method in which sinterable powder such as ceramic powder or metal powder is dispersed in a volatile liquid such as water to make a slurry, which is poured into a mold and then solidified (gelled), thereby forming the powder into a desired shape. Gel casting has the advantage that it is relatively easy to create molded bodies with complex shapes. The obtained gel wet molded body is then dried, degreased, and fired to become a sintered ceramic or metal product.
[0003] A method has been devised in which starch is used as an additive for solidifying a slurry in gel cast molding, as described in Patent Document 1, for example. The starch referred to here is starch that does not dissolve in cold water and becomes viscous by dissolving, decomposing, and swelling when heated (so-called beta starch). This starch does not dissolve in cold water and disperses in a particulate state, so it does not exhibit viscosity and can produce a slurry with high fluidity. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-302302 Summary of the Invention [Problem to be solved by the invention]
[0005] Sinterable powder slurries using starch take time to gel, and therefore there is a problem in that the starch particles present in the slurry before gelation settle, resulting in non-uniform gelation.
[0006] In view of the above, an object of an embodiment of the present invention is to provide a composition capable of improving the dispersion stability of starch particles. [Means for solving the problem]
[0007] The present invention includes the embodiments set forth below. [1] A composition containing fine fibrous cellulose, starch, and a sinterable powder, which satisfy the following conditions (a) to (d): (a) Number average fiber diameter is 2 nm or more and 500 nm or less (b) Average aspect ratio is between 30 and 1000 (c) Cellulose type I crystal structure (d) Having an anionic functional group [2] The composition described in [1], wherein the fine fibrous cellulose has a carboxy group as the anionic functional group. [3] The composition according to [1] or [2], wherein the mass ratio of starch / fine fibrous cellulose is 5 to 300, and the mass ratio of sinterable powder / fine fibrous cellulose is 100 to 2000. [4] The composition according to any one of [1] to [3], wherein the starch comprises at least one selected from the group consisting of starch derived from non-glutinous rice, starch derived from glutinous rice, starch derived from potato, and starch derived from corn. [5] The composition according to any one of [1] to [4], which is a slurry composition further containing water. [6] The composition according to any one of [1] to [5], which is for wet molding to produce a sintered body. [7] A method for producing a sintered body, comprising: preparing a gel wet compact by gelling starch by wet molding using the composition according to any one of [1] to [6]; and drying and sintering the gel wet compact. Effect of the Invention
[0008] According to an embodiment of the present invention, starch particles can be stably dispersed in a slurry and can be uniformly gelled. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The composition according to the embodiment contains fine fibrous cellulose (A), starch (B), and sinterable powder (C).
[0010] [Fine fibrous cellulose (A)] The fine fibrous cellulose (A) used satisfies the following conditions (a) to (d). (a) the number average fiber diameter is 2 nm or more and 500 nm or less; (b) the average aspect ratio is greater than or equal to 30 and less than or equal to 1,000; (c) having a cellulose I type crystal structure; and (d) Having an anionic functional group.
[0011] The cellulose I-type crystal structure is the crystal form of natural cellulose. The I-type crystal structure allows the fine fibrous cellulose (A) to be insoluble in water. Therefore, the fine fibrous cellulose (A) can maintain its fibrous form in a slurry containing water. In addition, since the fine fibrous cellulose (A) has an anionic functional group, it can easily obtain the above-mentioned elongated fibrous forms (a) and (b) by defibration. And, since the fine fibrous cellulose (A) that maintains its fibrous form in the slurry is elongated, the dispersion stability of starch particles in the slurry can be increased by entanglement between the fine fibers (nanofibers), and sedimentation can be suppressed, and uniform gelation can be achieved. In addition, the presence of the fine fibrous cellulose (A) allows the sinterable powder (C) to be stably dispersed in the slurry, and uniform gelation of the slurry is possible.
[0012] The number average fiber diameter of (a) is more preferably 50 nm or less, further preferably 30 nm or less, and may be 10 nm or less. The number average fiber diameter can be measured as follows.
[0013] That is, an aqueous dispersion of fine fibrous cellulose (A) with a solid content of 0.05 to 0.1% by mass is prepared, and the aqueous dispersion is cast on a carbon film-coated grid that has been hydrophilized to obtain a sample for observation with a transmission electron microscope (TEM). When the sample contains fibers with a large fiber diameter, a scanning electron microscope (SEM) image of the surface cast onto glass may be observed. The sample for observation may be negatively stained with, for example, 2% by mass uranyl acetate. Then, the sample is observed with an electron microscope image at a magnification of 5000 times, 10000 times, or 50000 times depending on the size of the fibers that constitute the sample. In this case, an arbitrary axis of the image width is assumed in the obtained image in the vertical and horizontal directions, and the sample and observation conditions (magnification, etc.) are adjusted so that 20 or more fibers cross the axis. After obtaining an observation image that satisfies this condition, two random axes are drawn vertically and horizontally on the image, and the fiber diameters of the fibers that cross the axis are visually read. In this way, at least three non-overlapping images of the surface area are taken with an electron microscope, and the fiber diameters of the fibers intersecting each of the two axes are read (thus, information on the diameters of at least 20 fibers x 2 x 3 = 120 fibers is obtained). The arithmetic mean of the fiber diameters obtained in this way is the number-average fiber diameter.
[0014] The average aspect ratio of (b) above is more preferably at least 50, further preferably at least 100, and may be at least 200. The average aspect ratio is more preferably at most 700, and may be at most 500. The average aspect ratio can be measured as follows.
[0015] That is, the number average fiber diameter is calculated according to the method described above. The number average fiber length of the fine fibrous cellulose (A) is also calculated from the same observation image. Specifically, the length from the start point to the end point of the fiber (fiber length) of at least 10 fibers is visually read. For branched fibers, the length of the longest part of the fiber is taken as the fiber length. The arithmetic mean of the fiber lengths thus obtained is calculated to be the number average fiber length. Using these values, the average aspect ratio is calculated according to the following formula. Average aspect ratio = number average fiber length (nm) / number average fiber diameter (nm)
[0016] The presence of the above (c) cellulose type I crystal structure can be identified by the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°, in the diffraction profile obtained by wide-angle X-ray diffraction image measurement.
[0017] The anionic functional group (d) may be, for example, at least one selected from the group consisting of a carboxyl group, a phosphate group, a sulfonic acid group, a nitrate group, a borate group, and a sulfate group. These anionic functional groups may be directly or indirectly bonded to a glucose unit, which is a structural unit of a cellulose molecule. When bonded indirectly, for example, an alkylene group having 1 to 4 carbon atoms may be present between the glucose unit and the anionic functional group.
[0018] In this specification, the term "carboxy group" refers not only to the acid type (-COOH) but also to the salt type, i.e., carboxylate group (-COOX, where X is a cation that forms a salt with a carboxylic acid), and the acid type and the salt type may be mixed. Similarly, the term "phosphate group, sulfonic acid group, nitrate group, borate group, and sulfate group" refers to the acid type and the salt type, and the acid type and the salt type may be mixed. The salt is not particularly limited, and examples thereof include alkali metal salts such as sodium salts and potassium salts, alkaline earth metal salts such as magnesium salts and calcium salts, onium salts such as ammonium salts and phosphonium salts, and amine salts such as primary amines, secondary amines, and tertiary amines.
[0019] The amount of anionic functional groups in the fine fibrous cellulose (A) is not particularly limited, and may be, for example, 0.5 to 3.0 mmol / g or 1.0 to 2.5 mmol / g per dry mass of the fine fibrous cellulose (A). For example, in the case of a carboxy group, the amount of anionic functional groups can be calculated by preparing 60 mL of a slurry containing fine fibrous cellulose adjusted to a concentration of 0.1 to 1% by mass, adjusting the pH to about 2.5 with a 0.1 mol / L aqueous hydrochloric acid solution, dropping a 0.05 mol / L aqueous sodium hydroxide solution, measuring the electrical conductivity, and continuing until the pH becomes about 11. The amount of sodium hydroxide (V) consumed in the neutralization stage of the weak acid where the change in electrical conductivity is gradual can be calculated according to the following formula. The amount of phosphate groups can also be measured by the same electrical conductivity measurement. Other anionic functional groups may also be measured by a known method. Amount of anionic functional group (mmol / g) = V (mL) × [0.05 / mass of fine fibrous cellulose (g)]
[0020] In one embodiment, the fine fibrous cellulose (A) preferably has a carboxy group as an anionic functional group. Examples of the fine fibrous cellulose containing a carboxy group include fine fibrous oxidized cellulose obtained by oxidizing the hydroxyl groups of the glucose units in the cellulose molecule, and fine fibrous carboxymethylated cellulose obtained by carboxymethylating the hydroxyl groups of the glucose units in the cellulose molecule.
[0021] An example of fine fibrous oxidized cellulose is cellulose in which the hydroxyl group at the C6 position of the glucose unit in the cellulose molecule is selectively oxidized to a carboxyl group. Fine fibrous oxidized cellulose can be obtained by oxidizing natural cellulose such as wood pulp using a co-oxidant in the presence of an N-oxyl compound and subjecting it to defibration (fineness) treatment. As the N-oxyl compound, a compound having a nitroxy radical that is generally used as an oxidation catalyst is used, for example, a piperidine nitroxyoxy radical, and in particular, 2,2,6,6-tetramethylpiperidinooxy radical (TEMPO) or 4-acetamide-TEMPO is preferred. Fine fibrous cellulose oxidized with TEMPO is generally called TEMPO oxidized cellulose nanofiber (TOCN). The fine fibrous oxidized cellulose may have an aldehyde group or a ketone group in addition to the carboxyl group.
[0022] The fine fibrous cellulose (A) may be obtained by defibration treatment. The defibration treatment may be carried out after or before the introduction of an anionic functional group. The defibration treatment may be carried out by treating an aqueous dispersion of cellulose fibers using, for example, a homomixer, a high-pressure homogenizer, an ultrasonic dispersion processor, a beater, a disk refiner, a conical refiner, a double disk refiner, a grinder, or the like under high-speed rotation, to obtain an aqueous dispersion of the fine fibrous cellulose (A).
[0023] [Starch (B)] Starch (B) is used as a gelling agent, and it is preferable to use one that disperses in cold water as described above and dissolves and gels when heated. For example, it is preferable to use β (beta) starch in a natural crystalline state, that is, natural crystalline starch. As a result, even when the composition according to this embodiment is a slurry composition containing water, starch (B) is dispersed in water without dissolving, that is, exists in a particulate form as starch particles.
[0024] The plant from which starch (B) is derived is not particularly limited, and examples thereof include rice, potato, corn, broad bean, mung bean, adzuki bean, sweet potato, taro, tapioca, etc., and starches derived from these plants may be used alone or in combination of two or more. Preferably, at least one selected from the group consisting of starch derived from non-glutinous rice, starch derived from glutinous rice, starch derived from potato, and starch derived from corn is used.
[0025] The particle size of the starch (B) is not particularly limited, and may be, for example, one having an average particle size of 0.1 μm or more and 100 μm or less, or one having an average particle size of 1 μm or more and 80 μm or less. According to this embodiment, by blending the fine fibrous cellulose (A), even if the particle size of the starch (B) is relatively large, the starch (B) can be stably dispersed and maintained in the slurry. The average particle size of the starch (B) is a value (D50: measured value of the particle size at 50% of the cumulative value in the particle size distribution) measured by wet measurement based on the laser diffraction scattering method using a particle size distribution measuring device (e.g., Microtrac MT3300EXII, Nikkiso Co., Ltd.).
[0026] [Sinterable powder (C)] The sinterable powder (C) is a powder that is a material for forming a sintered body, and examples thereof include inorganic powders (that is, sinterable inorganic powders) such as ceramic powders and metal powders.
[0027] A specific example of ceramic powder is Al 2 O 3 , BeO, ZrO 2 , MgO, titanium oxide, mullite, cordierite, forsterite, steatite, ferrite, oxides such as aluminum titanate, SiC, TiC, ZrC, B 4 C, carbides such as WC, CrB, ZrB 2 Borides such as Si 3 N 4Examples of the metal powder include powders of nitrides such as TiN and ZrN. Specific examples of the metal powder include powders of iron, tungsten, copper, molybdenum, cobalt, nickel, aluminum, or alloys containing these as main components. These may be used alone or in combination of two or more.
[0028] The particle size of the sinterable powder (C) is not particularly limited, and may be, for example, an average particle size of 0.1 μm to 500 μm, 1 μm to 100 μm, or 1 μm to 50 μm. The average particle size of the sinterable powder (C) is a value (D50: measured value of particle size at 50% of the cumulative value in the particle size distribution) measured by dry measurement based on the laser diffraction scattering method using a particle size distribution measuring device (e.g., Microtrac MT3300EXII, Nikkiso Co., Ltd.).
[0029] [Water(D)] The composition according to this embodiment may further contain water, and is usually used for wet molding as a slurry composition containing water.
[0030] [Composition] In the composition according to the present embodiment, the content of each of the above components is not particularly limited, but it is preferable that the starch / fine fibrous cellulose (mass ratio of starch (B) to fine fibrous cellulose (A)) is 5 to 300. Also, it is preferable that the sinterable powder / fine fibrous cellulose (mass ratio of sinterable powder (C) to fine fibrous cellulose (A)) is 100 to 2000. When the starch / fine fibrous cellulose is 5 or more, the strength of the gel wet molding after wet molding can be increased. When the starch / fine fibrous cellulose is 2000 or less, the dispersion stability of the starch in the slurry can be increased. When the sinterable powder / fine fibrous cellulose is 100 or more, the strength of the sintered body can be increased. When the sinterable powder / fine fibrous cellulose is 2000 or less, the dispersion stability of the sinterable powder in the slurry can be increased.
[0031] The ratio of starch / fine fibrous cellulose is more preferably 10 to 200, and further preferably 25 to 100. The ratio of sinterable powder / fine fibrous cellulose is more preferably 150 to 1,500, and further preferably 300 to 1,000.
[0032] The mass ratio of sinterable powder (C) to starch (B) (i.e., sinterable powder / starch) is not particularly limited, but is preferably 1 to 100. When sinterable powder / starch is 1 or more, the strength of the sintered body can be increased. When sinterable powder / starch is 100 or less, the strength of the gel wet compact after wet molding can be increased. The sinterable powder / starch ratio is more preferably 3 to 50, and even more preferably 5 to 30.
[0033] The composition according to the present embodiment may be a powder composition not containing water, or may be a slurry composition obtained by adding water. The method for preparing the slurry composition containing fine fibrous cellulose (A), starch (B), sinterable powder (C) and water (D) is not particularly limited. For example, starch (B) may be added and mixed into an aqueous dispersion of fine fibrous cellulose (A) to obtain an aqueous dispersion of fine fibrous cellulose (A) and starch (B), and then sinterable powder (C) may be added and mixed into the aqueous dispersion to prepare a slurry. Alternatively, sinterable powder (C) may be added and mixed into an aqueous dispersion of fine fibrous cellulose (A) to prepare a slurry, and then starch (B) may be added and mixed into the slurry. Alternatively, fine fibrous cellulose (A) and starch (B), or aqueous dispersions thereof, may be added and mixed into a slurry obtained by dispersing sinterable powder (C) in water. Alternatively, a powdery composition containing the fine fibrous cellulose (A), starch (B) and sinterable powder (C) may be mixed with water (D) to prepare a slurry.
[0034] In the above slurry composition, the content of each component is not particularly limited. The preferred mass ratios of starch / fine fibrous cellulose, sinterable powder / fine fibrous cellulose, and sinterable powder / starch are as described above. The content of the sinterable powder (C) relative to 100% by mass of the slurry composition is preferably 35-75% by mass, more preferably 50-70% by mass. The content of water (D) relative to 100% by mass of the slurry composition is preferably 10-50% by mass, more preferably 20-40% by mass.
[0035] According to this embodiment, by blending the fine fibrous cellulose (A), the settling of starch particles can be suppressed without a high concentration of the sinterable powder (C). That is, if the fine fibrous cellulose (A) is not blended, in a slurry composition using starch (B) that requires a long time for gelation, the starch particles tend to settle and the gelation tends to be non-uniform. To solve this problem, for example, if a high concentration of the sinterable powder (C) is added, the settling of starch particles can be suppressed, but the fluidity of the slurry composition decreases, making it difficult to put into a mold during wet molding. In contrast, according to this embodiment, by blending the fine fibrous cellulose (A), the settling of starch particles can be suppressed without a high concentration of the sinterable powder (C), and the fluidity of the slurry composition can be increased.
[0036] In addition to the above-described components (A) to (D), the composition according to this embodiment may further contain additives such as a dispersant, a plasticizer, a porosifying agent, a surfactant, a sintering aid, an organic solvent, a thickener, a binder, and a lubricant, provided that the effects of this embodiment are not impaired.
[0037] The dispersant may be used in advance to treat the sinterable powder (C) in order to make it easier to disperse the sinterable powder (C) in water. Examples of such dispersants include ammonium polyacrylate and ammonium acrylate copolymers. The content of the dispersant is not particularly limited, and may be, for example, 0.1 to 10 parts by mass or 0.2 to 5 parts by mass relative to 100 parts by mass of the sinterable powder (C).
[0038] The composition according to the present embodiment is preferably used as a wet molding composition for producing a sintered body. In this case, the starch (B) is used as a gelling agent (wet molding gelling agent) for solidifying (gelling) the molded body obtained by wet molding. Such a wet molding gelling agent contains the fine fibrous cellulose (A) together with the starch (B), and may be a dispersion liquid further containing water (D).
[0039] [Method of manufacturing sintered body] A method for producing a sintered body according to one embodiment includes preparing a gel wet compact by gelling starch (B) by wet molding using the composition according to the above embodiment, and drying and firing the gel wet compact.
[0040] As a preferred example, when a sintered body is produced by gel casting, the following steps are included. (1) pouring the slurry composition into a mold; (2) A step of heating and solidifying (gelling) the mixture in a mold to obtain a gel wet molded body; (3) drying the obtained gel wet molding; and (4) A step of firing the dried green body.
[0041] Step (1) is a casting step in which the slurry composition is poured into a water-impermeable mold, and may be mechanically stirred to introduce air bubbles into the slurry composition, thereby obtaining a porous gel wet compact in step (2), and finally a porous sintered body.
[0042] In addition to the mechanical stirring, the porous sintered body can be obtained by mixing a foaming agent as a porosity agent into the slurry composition, and introducing bubbles into the slurry composition by foaming with the foaming agent. Alternatively, a porous sintered body can be obtained by mixing particles made of an organic substance that disappears by pyrolysis during firing into the slurry composition as a porosity agent, and disappearing the particles during firing.
[0043] In step (2), the starch (B) in the slurry composition is heated to dissolve and solidify (gel) in the mold, thereby obtaining a gel wet compact containing water. The heating temperature for gelation is not particularly limited, and may be, for example, 70 to 90°C.
[0044] The step (3) is a step of pre-drying the gel wet molded body, in which the moisture contained in the gel wet molded body is substantially removed. The drying temperature is not particularly limited, and may be, for example, 40 to 100°C.
[0045] Step (4) is a step of firing the dried molded body, and degreasing is usually performed before firing. Degreasing is a step of removing organic matter by pyrolysis by heating the dried molded body, and organic matter such as fine fibrous cellulose (A) and starch (B) contained in the molded body is removed. The heating temperature in the degreasing step is not particularly limited, and may be, for example, 450 to 550°C.
[0046] The firing step is a step of sintering the sinterable powder (C) to obtain a sintered body, and the treatment conditions may be appropriately set according to the type of sinterable powder (C), etc. For example, the heating temperature during firing may be 1400 to 1600°C when the sinterable powder (C) is a ceramic powder, and may be 1200 to 1400°C when the sinterable powder (C) is a metal powder.
[0047] By the above firing, a ceramic product or a metal product can be obtained as a sintered body.
[0048] The method for producing the above-mentioned gel wet molded body is not limited to gel cast molding, and various wet molding methods can be used as long as the gel wet molded body can be obtained by molding a slurry composition into a predetermined shape and gelling it. For example, a sheet-shaped gel wet molded body may be produced by adding a plasticizer to the slurry composition and molding the slurry composition into a sheet.
[0049] The various numerical ranges including the above-mentioned content and particle size can be arbitrarily combined with their upper and lower limits, and all such combinations are considered to be preferred numerical ranges and are described in this specification. EXAMPLES
[0050] The present invention will be explained in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0051] <Preparation of fine fibrous cellulose> The fine fibrous celluloses A1 and A2 for the examples and the fine fibrous celluloses A3 and A4 for the comparative examples were prepared according to Production Examples 1 to 4 below.
[0052] [Production Example 1: Fine fibrous cellulose A1] 150 mL of water, 0.25 g of sodium bromide, and 0.025 g of TEMPO were added to 2 g of softwood pulp, thoroughly stirred to disperse the mixture, and then a 13% by mass aqueous solution of sodium hypochlorite was added so that the amount of sodium hypochlorite was 6.5 mmol / g per 1.0 g of the pulp, and the reaction was carried out. Since the pH decreased as the reaction proceeded, a 0.1 M aqueous solution of sodium hydroxide was added dropwise to maintain the pH at 10 to 11, and the reaction was continued until no change in pH was observed (reaction time: 120 minutes). After the reaction was completed, 1 M hydrochloric acid was added to make the pH acidic, and the solid-liquid separation was performed using a centrifuge, and pure water was added to prepare a slurry with a solid concentration of 4% by mass. The pH of the slurry was then adjusted to 10 with a 1 M aqueous solution of sodium hydroxide. The temperature of the slurry was raised to 30°C, and sodium borohydride was added at 0.2 mmol / g relative to the cellulose fibers, and the mixture was reacted for 2 hours for reduction treatment. After the reaction, the mixture was neutralized by adding 1M hydrochloric acid, and purified by repeated filtration and washing with water to obtain TEMPO-oxidized cellulose fibers. The obtained TEMPO-oxidized cellulose fibers were diluted with pure water to 2% by mass, and the pH of the solution was adjusted to 7 with 1M aqueous sodium hydroxide solution. The solution was treated once at a pressure of 100 MPa using a high-pressure homogenizer (L-01, manufactured by Sanwa Engineering Co., Ltd.) to obtain an aqueous dispersion of fine fibrous cellulose A1.
[0053] [Production Example 2: Fine fibrous cellulose A2] An aqueous dispersion of fine fibrous cellulose A2 was obtained in the same manner as in the preparation of fine fibrous cellulose A1, except that the amount of the aqueous sodium hypochlorite solution added was 12.0 mmol / g per 1.0 g of the pulp.
[0054] [Production Example 3: Fine fibrous cellulose A3] 50 g of bleached softwood kraft pulp (NBKP) was dispersed in 4950 g of water to prepare a dispersion with a pulp concentration of 2% by mass. This dispersion was treated 30 times with a Supermass Colloider (MKCA6-3, manufactured by Masuko Sangyo Co., Ltd.) to obtain an aqueous dispersion of fine fibrous cellulose A3.
[0055] [Production Example 4: Fine fibrous cellulose A4] An aqueous dispersion of fine fibrous cellulose A4 was obtained in accordance with the preparation method of fine fibrous cellulose A1, except that regenerated cellulose was used instead of the raw material coniferous pulp and the amount of sodium hypochlorite aqueous solution added was 27.0 mmol / g per 1.0 g of regenerated cellulose.
[0056] The obtained fine fibrous celluloses A1 to A4 were measured for the presence or absence of cellulose I type crystal structure, the number average fiber diameter, the aspect ratio, the amount of carboxyl groups, and the amount of carbonyl groups. The measurement methods were as follows, and the results are shown in Table 1 below.
[0057] [Crystal structure] The diffraction profile of the fine fibrous cellulose was measured using an X-ray diffraction device (Rigaku Corporation, RINT-Ultima3). If typical peaks were observed at two positions, around 2θ = 14° to 17° and 2θ = 22° to 23°, the crystal structure (cellulose type I crystal structure) was evaluated as "present," and if no peaks were observed, it was evaluated as "absent."
[0058] [Measurement of number average fiber diameter and average aspect ratio] The number average fiber diameter and number average fiber length of the fine fibrous cellulose were observed using a transmission electron microscope (TEM, JEM-1400 manufactured by JEOL Ltd.). That is, an aqueous dispersion of fine fibrous cellulose was cast onto a hydrophilically treated carbon membrane-coated grid, and then a TEM image (magnification: 10,000 times) was obtained by negatively staining with 2% by mass uranyl acetate. From the obtained image, the number average fiber diameter and number average fiber length were calculated according to the method described above. Furthermore, the average aspect ratio was calculated using these values.
[0059] [Measurement of carboxyl group amount] 0.25 g of fine fibrous cellulose was weighed out into a 100 mL beaker, and the pH was adjusted to approximately 2.5 with 40 mL of water and 0.1 M aqueous hydrochloric acid, after which 0.05 M aqueous sodium hydroxide was added dropwise and electrical conductivity was measured. Measurements were continued until the pH reached approximately 11. The amount of carboxyl groups was calculated from the amount of sodium hydroxide (V) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual, using the following formula. Amount of carboxyl group (mmol / g) = V (mL) × [0.05 / mass of fine fibrous cellulose (g)]
[0060] [Measurement of carbonyl group content] Approximately 0.2 g of fine fibrous cellulose was weighed out, and 50 mL of a 3 g / L aqueous solution of semicarbazide hydrochloride adjusted to pH = 5 with a phosphate buffer was added, sealed, and shaken for two days. Next, 10 mL of this solution was taken into a 100 mL beaker, and 25 mL of 5 M sulfuric acid and 5 mL of 0.05 M potassium iodate aqueous solution were added, and the mixture was stirred for 10 minutes. Then, 10 mL of a 5 mass% aqueous potassium iodide solution was added, and immediately titrated with a 0.1 M sodium thiosulfate solution using an automatic titrator. The amount of carbonyl groups in the sample (the total content of aldehyde groups and ketone groups) was calculated from the titration amount, etc., according to the following formula. Amount of carbonyl groups (mmol / g) = (DB) × f × (0.125 / w) D: titer of sample (mL) B: Titration volume of blank test (mL) f: Factor of 0.1M sodium thiosulfate solution w: sample amount (g)
[0061] [Table 1]
[0062] As shown in Table 1, fine fibrous cellulose A1 and A2 were TEMPO-oxidized cellulose nanofibers having a cellulose type I crystal structure and carboxyl groups as anionic functional groups. On the other hand, fine fibrous cellulose A3 had a cellulose type I crystal structure, but had a small average aspect ratio, and both the carboxyl group amount and the carbonyl group amount were below the detection limit. Fine fibrous cellulose A4 did not have a cellulose type I crystal structure and was dissolved in water, so the number average fiber diameter and average aspect ratio could not be measured.
[0063] <Evaluation of gelling agents for wet molding> [Example 1] Water was added to the fine fibrous cellulose A1 aqueous dispersion (cellulose solid content 2% by mass), and the mixture was stirred for 10 minutes with a homomixer (manufactured by Primix, rotation speed: 5000 rpm) to dilute the mixture to a cellulose solid content of 0.33% by mass. Then, 10 g of potato-derived starch (manufactured by Wako Pure Chemical Industries, Ltd., average particle size: 60 μm) was added to 100 g of the fine fibrous cellulose A1 aqueous dispersion (cellulose solid content 0.33% by mass), and the mixture was stirred for 1 minute with a planetary centrifugal mixer (manufactured by Thinky Co., Ltd., AR-250) to obtain a gelling agent for wet molding consisting of an aqueous dispersion. A stability test over time and a uniform gelling test were performed on the gelling agent for wet molding.
[0064] [Examples 2 to 10, Comparative Examples 1 to 6] A wet molding gelling agent was prepared in the same manner as in Example 1, except that the type and concentration of fine fibrous cellulose and the type and parts by mass of starch were changed as shown in Tables 2 and 3 below. A stability test over time and a uniform gelling test were carried out. In Comparative Examples 3 to 6, the same amount of water was added instead of the aqueous dispersion of fine fibrous cellulose.
[0065] Regarding the types of starch in Tables 2 and 3, "corn" is corn-derived starch (manufactured by Wako Pure Chemical Industries, Ltd., average particle size: 50 μm), "non-glutinous rice" is non-glutinous rice-derived starch (manufactured by Joetsu Starch Co., Ltd., Fine Snow, average particle size: 5 μm), and "glutinous rice" is glutinous rice-derived starch (manufactured by Joetsu Starch Co., Ltd., Motil B, average particle size: 5 μm).
[0066] The methods for the temporal stability test and uniform gelation test for the wet molding gelling agent are as follows, and the results are shown in Tables 2 and 3.
[0067] [Stability test over time] 10 mL of the wet molding gelling agent was placed in a test tube, and after leaving it to stand at room temperature for 1 hour, it was confirmed whether precipitation of starch particles occurred. If the starch particles were uniformly dispersed, it was rated as "Good", and if precipitation occurred, it was rated as "Poor".
[0068] [Uniform gelation test] 10 mL of wet molding gelling agent was placed in a 20 mL plastic container, heated at 80°C for 1 hour, and then returned to room temperature to check whether gelling had progressed uniformly. Gelling was confirmed by turning the plastic container upside down and checking the state of the contents. Cases where gelling had progressed uniformly were rated as "Good," and cases where gelling had progressed partially were rated as "Poor."
[0069] [Table 2]
[0070] [Table 3]
[0071] From Tables 2 and 3, it was found that in Examples 1 to 10, the dispersion of starch particles was better and the starch was uniformly gelled compared to Comparative Examples 1 to 6. These Examples are the evaluation results for an aqueous dispersion that did not contain sinterable powder (C), but considering that the fine fibrous cellulose inhibits the settling of starch particles in the aqueous dispersion and the starch particles are stably dispersed over time, it is considered that the settling of starch particles is also inhibited in a slurry containing sinterable powder (C), and therefore, even if it takes time for the slurry to gel and even if the concentration of sinterable powder (C) is low, it is considered that the starch particles can be uniformly gelled without settling.
[0072] In contrast, Comparative Example 1 contains fine fibrous cellulose, but is not anion-modified, and has a small average aspect ratio, so it is difficult to stably disperse starch particles, and it is believed that the starch could not be uniformly gelled. Comparative Example 2 uses cellulose fibers that do not have a cellulose I type crystal structure, and the cellulose fibers are dispersed in water without agglomeration, but it is difficult to stably disperse starch particles, and it is believed that the starch could not be uniformly gelled. Comparative Examples 3 to 6 do not contain fine fibrous cellulose, so it is difficult to stably disperse starch particles, and it is believed that the starch could not be uniformly gelled.
[0073] Here, Examples 1 and 2 show the results when different fine fibrous celluloses were used. Examples 2, 3 to 5, 9, and 10 show the results when at least one of the fine fibrous cellulose concentration and the starch concentration is different. Examples 2, 6 to 8 show the results when different starches were used.
[0074] <Evaluation of wet molding slurry composition> [Example 11] 25 g of distilled water (1) and 0.2 g of dispersant (Aron A-6114, Toa Gosei Co., Ltd.) were added to 100 g of alumina (manufactured by Fujimi Incorporated Co., Ltd., WA#1500, average particle size: 8.5 μm) to prepare an alumina slurry. 10 g of the fine fibrous cellulose A1 aqueous dispersion (cellulose solid content 2 mass%) prepared in Production Example 1, 10 g of potato-derived starch (manufactured by Wako Pure Chemical Industries, Ltd., average particle size: 60 μm), and 25 g of distilled water (2) were added to the above alumina slurry, and the mixture was stirred for 3 minutes with a planetary centrifugal mixer (manufactured by Thinky Co., Ltd., AR-250) to obtain a wet compacting slurry composition. The obtained wet compacting slurry composition was evaluated for dispersion stability of the alumina powder and dimensional stability after sintering.
[0075] [Examples 12 to 17, Comparative Examples 7 to 9] The type and amount of the fine fibrous cellulose, the type and amount of starch, and the amount of distilled water (1) and (2) added were changed as shown in Table 4 below. Otherwise, a wet compacting slurry composition was prepared in the same manner as in Example 11, and the dispersion stability of the alumina powder was evaluated, as well as the dimensional stability after sintering.
[0076] The dispersion stability of the alumina powder in the wet compacting slurry composition and the dimensional stability after sintering were evaluated as follows. The results are shown in Table 4.
[0077] [Dispersion stability of alumina powder] 10 mL of the wet molding slurry composition was placed in a test tube, left to stand at room temperature for 1 hour, and then it was confirmed whether precipitation of the alumina powder occurred. If the alumina powder was uniformly dispersed, it was rated as "Good", and if precipitation occurred, it was rated as "Poor".
[0078] [Dimensional stability after sintering] 40 mL of the wet molding slurry composition was added to a 100 mL disposable cup, and gelled at 80°C for 1 hour to obtain a gel wet compact. The obtained gel wet compact was removed from the disposable cup, dried at 40°C for 24 hours, and then degreased in air at 500°C for 3 hours. After degreasing, the product was fired in air at 1600°C for 3 hours to obtain a sintered body. The obtained sintered body was checked for cracks, and was rated as "good" if there were no cracks and "bad" if there were cracks.
[0079] [Table 4]
[0080] As shown in Table 4, it was found that in Examples 11 to 17, the dispersion stability of the starch particles and the alumina powder was better than that in Comparative Examples 7 to 9, and a sintered body without cracks was obtained by uniform gelation. In Comparative Example 7, it is considered that it was difficult to stably disperse the starch particles and the alumina powder because the fine fibrous cellulose did not have a cellulose I type crystal structure, and uniform gelation was not possible, resulting in a sintered body with cracks. In Comparative Examples 8 and 9, it is considered that it was difficult to stably disperse the starch particles and the alumina powder because the fine fibrous cellulose was not added, and uniform gelation was not possible, resulting in a sintered body with cracks.
[0081] Although several embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the gist of the invention. These embodiments and their omissions, substitutions, modifications, etc. are included in the scope and gist of the invention as well as the invention and its equivalents described in the claims.
Claims
1. A gel cast slurry composition containing fine fibrous cellulose, starch particles, a sinterable powder, and water, which satisfies the following conditions (a) to (d): (a) Number average fiber diameter is 2 nm or more and 500 nm or less (b) an average aspect ratio of 30 to 1,000 (c) Cellulose having type I crystal structure (d) Having an anionic functional group
2. 2. The gel cast slurry composition according to claim 1, wherein the fine fibrous cellulose has a carboxy group as the anionic functional group.
3. 3. The gel cast molding slurry composition according to claim 1, wherein the mass ratio of starch particles to fine fibrous cellulose is 5 to 300, and the mass ratio of sinterable powder to fine fibrous cellulose is 100 to 2000.
4. The gel cast molding slurry composition according to any one of claims 1 to 3, wherein the starch particles contain at least one kind selected from the group consisting of starch derived from non-glutinous rice, starch derived from glutinous rice, starch derived from potato, and starch derived from corn.
5. A method for producing a sintered body, comprising: preparing a gel wet compact by gel casting using the gel cast slurry composition according to any one of claims 1 to 4 to gelatinize the starch particles; and drying and firing the gel wet compact.
Citation Information
Patent Citations
Production of formed ceramic material having high density
JP1995033534A
Starch for gel cast molding and molding using the same
JP1999302302A
Composition for wet molding of ceramic and method for producing wet molding
JP2019172535A